2021
DOI: 10.1364/boe.437981
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of scleral mechanical properties from air-puff optical coherence tomography

Abstract: We introduce a method to estimate the biomechanical properties of the porcine sclera in intact eye globes ex vivo, using optical coherence tomography that is coupled with an air-puff excitation source, and inverse optimization techniques based on finite element modeling. Air-puff induced tissue deformation was determined at seven different locations on the ocular globe, and the maximum apex deformation, the deformation velocity, and the arc-length during deformation were quantified. In the sclera, the experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…But the corneal biomechanical asymmetry between anisometropic eyes may be limited by the same genetic background. Thirdly, even though cornea and scleral are a whole, their biomechanical behaviors are still different when stress is applied ( Bronte-Ciriza et al, 2021 ), thus corneal biomechanical measures may not fully represent the scleral biomechanics.…”
Section: Discussionmentioning
confidence: 99%
“…But the corneal biomechanical asymmetry between anisometropic eyes may be limited by the same genetic background. Thirdly, even though cornea and scleral are a whole, their biomechanical behaviors are still different when stress is applied ( Bronte-Ciriza et al, 2021 ), thus corneal biomechanical measures may not fully represent the scleral biomechanics.…”
Section: Discussionmentioning
confidence: 99%
“… 49 Whereas the intact eye in inflation tests more closely approximates physiological conditions, the scleral properties reconstructed from inflation tests are necessarily influenced by assumptions regarding the cornea 51 , 52 and ocular tissues as well as the preconditioning response during inflation. 50 Conversely, the tensile test provides us with a direct quantification of the YM of tissues that other techniques can only obtain through inverse viscoelastic reconstruction techniques from air-puff deformation 23 , 24 , 53 or OCE measurements. 40 , 42 In addition, some studies have identified a preferential orientation of scleral collagen fibers.…”
Section: Discussionmentioning
confidence: 99%
“…OCE measurements were performed using a phase-sensitive sweptsource optical coherence tomography (PhS-SS-OCT) system combined with an air-coupled ultrasonic tissue excitation transducer [3]. The PhS-SS-OCT is a custom-built system with a swept source centered at 1300 nm and an axial scan rate of 200 kHz [4,5]. The system provides multi-meridian scanning functionality, which was used to acquire 8 meridians (16 semi-axes) of 15 mm length evenly distributed over 360 degrees (0°-337.5° in 22.5° steps).…”
Section: Multi-meridian Air-coupled Ultrasonic Optical Coherence Elas...mentioning
confidence: 99%